1996
DOI: 10.1007/bf01875419
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive functioning in chronic fatigue syndrome

Abstract: Although substantial research has been conducted on chronic fatigue syndrome (CFS) over the past decade, the syndrome remains poorly understood. The most recent case definition describes CFS as being characterized both by disabling fatigue and by subjective reports of difficulty with concentration and "short-term" memory. However, research into the neurocognitive and psychological functioning of individuals with CFS has provided mixed objective results. The current paper reviews studies that have examined the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Our measure of digit learning did not yield a significant difference, but there was a group difference in number correct on the ODTP. Our findings appear to be consistent with findings in nonveteran CFS samples as reviewed recently (DiPino & Kane, 1996;Tiersky et al, 1997).…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Our measure of digit learning did not yield a significant difference, but there was a group difference in number correct on the ODTP. Our findings appear to be consistent with findings in nonveteran CFS samples as reviewed recently (DiPino & Kane, 1996;Tiersky et al, 1997).…”
Section: Resultssupporting
confidence: 93%
“…Although the etiology of CFS in the general population is of unknown origin and may be psychiatric, it is clear that there are neuropsychological deficits associated with the illness (DiPino & Kane, 1996;Tiersky et al, 1997). Tiersky et al concluded that complex information processing speed and efficiency were the primary areas of cognitive deficit.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this review paper is to provide for a pattern of results with respect to attention and memory function in CFS patients based on the most consistent findings. Former reviews on neurocognitive function in CFS have discussed objective neuropsychological performance by grouping the results into broad categories such as: the use of comparison groups or test norms ( 13); cognitive tests showing significant difference or non‐significance between CFS subjects and control subjects ( 14). Two have used neuropsychological categories.…”
Section: Introductionmentioning
confidence: 99%
“…A sizeable proportion of aviation accidents are also related to mental fatigue involving both the ight and ground support crews, and duty length ( ights time plus time needed for brie ngs, and administration), mental workload, and sleep loss were identi ed as important risk factors [30]. Moreover, mental fatigue is common among patients with chronic conditions such as multiple sclerosis, Parkinson's disease, and myalgic encephalomyelitis [4,6,31]. In addition to the perceived cognitive insu ciency (indicating trait mental fatigue) reported by many of these patients, they also display objective inability to adequately perform cognitive tasks due to mental fatigue which can negatively affect their daily activities, employment, social life, and quality of life [4,6,10,11,[31][32][33][34].…”
Section: Introductionmentioning
confidence: 99%